Surface chemical-functionalization of ultrathin two-dimensional nanomaterials for electrocatalysis. (June 2019) - Chen, Dawei; Zou, Yuqin; Wang, Shuangyin
Abstract: In the past few decades, with the development of energy conversion and storage technology, two-dimensional (2D) ultrathin nanomaterials with single or few atomic layers have been extensively studied as efficient electrocatalysts due to their unique physical, chemical, and electronic properties. The unique ultrathin structure provides an alternative way of modifying the surface phase or electronic structure for engineering the intrinsic electrocatalysts properties. Here, we focus on recent attempts to discuss the concerning surface chemical modification strategies of surface atoms incorporation, defect engineering, and surface structure modulation, which could respectively enhance the intrinsic electrical conductivity, optimizing the reaction energy barrier while maintaining the primary 2D structural stability. Following this review, we listed the surface-functional 2D materials for enhanced electrocatalytic processes involved in the water splitting, oxygen/nitrogen reduction reactions, as well as density functional theoretical (DFT) calculation to study the relationship between electronic structure, adsorption energy, and apparent activity sites. Finally, we also present some challenges and opportunities of surface chemical-functionalization of ultrathin 2D nanomaterials for electrocatalysis. Highlights: Two-dimensional materials show promising potential for electrocatalysis applications. The surface functionalization is an important strategy to improve the catalytic performance. The defect engineering works well for electrocatalysis.